Characteristics of Patients with Laryngomalacia: A Tertiary Referral Center Experience of 106 Cases - Sergii Bredun; Michal Kotowski; Jakub Mezydlo; Jaroslaw Szydlowski (Diagnostics, 2023)
Laryngomalacia (LM) is the most common airway congenital anomaly and the main cause of stridor in infants. Some patients with severe airway symptoms or with feeding difficulties require surgical intervention. Synchronous airway lesions (SALs) may influence the severity and course of the disease. This study aimed to determine the prevalence of various types of LM and SALs and their influence on surgical intervention decisions and feeding difficulties. Moreover, the study focused on the interrelations between SALs and the type of LM or the presence of feeding difficulties. A retrospective analysis of 106 pediatric patients revealed a significant relationship between type 2 LM and the necessity of surgical treatment. We also found a significant effect of LM type 2 on feeding difficulty. Type 1 LM is significantly more characteristic in premature children. Among different comorbidities, SALs are suspected of modification of the course and severity of LM. This study did not find a significant effect of SALs on the incidence of supraglottoplasty or feeding difficulty.